Pengaruh Model Pembelajaran Berbasis Gaya Belajar Visual Terhadap Prestasi Belajar Materi Sholat Idain Pada Peserta Didik MIN 1 Aceh Jaya - Encang Sarip Hidayat; Ainal Mardhiah (Concept: Journal of Social Humanities and Education, 2024)
The more appropriate the learning design is to students' learning styles, the more student learning outcomes will improve. The aim of this research is to describe the influence of learning designs based on visual learning styles on the learning outcomes of students with visual, auditory and kinesthetic learning styles. Qualitative descriptive research method with experimental design. The results of data analysis show that: 1. MIN 1 Aceh Jaya students have 3 learning styles, namely visual learning style, auditory learning style, and kinesthetic learning style. 2. Students with a visual learning style have an average score of 54 to 91.6. The average score for children with auditory learning is 45.7-46.8. And the average score for kinesthetic children ranges from 59.5 to 70. This shows that a learning design based on a visual learning style can improve the learning outcomes of students who only have a visual learning style.